ACCESSING THE LEVEL OF TOTAL PRODUCTIVE MAINTENANCE IMPLEMENTATION: THE CASE OF A NIGERIAN FABRICATION COMPANY - Ikechukwu John Ezemenike,; Harold Ugochukwu Nwosu,; Shadrach Matthew Uzoma, (International Journal of Innovations in Engineering Research and Technology, 2023)
The maintainability and reliability of manufacturing systems plays an important role in accessing both the quality and quantity of the products. However, practicing unscheduled preventive maintenance approach can pose high cost to the firm which can adversely minimize the reliability of the manufacturing line. This work is aimed at optimizing the overall total productive maintenance of a manufacturing system. A model was proposed to optimize the OEE value for the fabrication company. The OEE of the firm factor by factor before and after implementation of the MINLP and TPM-TQM-OEE model was assessed. After six months of implementation, the availability is 87% which is about 10.2% improvement, the performance ratio is 91% which is about 10.4% improvement and the quality ratio is 93% which is about 9.6% improvement as compared to the values of OEE factors before implementation. The OEE value also increased from 56% to 75% which is about 33% improvement. This research also tried to identify the most significant factor of OEE using the TPM-TQM-OEE model. The result showed that the OEE is mostly influenced by Availability (about 88%), followed by Performance rate (about 85%) and finally by Quality rate (about 82%). Reliability analysis among other analysis should always be considered during optimization maintenance practices.